Genetic Analyses of Cell-Free DNA in Pancreatic Juice or Bile for Diagnosing Pancreatic Duct and Biliary Tract Strictures - Kosuke Nagai; Masaki Kuwatani; Koji Hirata; Goki Suda; Hajime Hirata; Yunosuke Takishin; Ryutaro Furukawa; Kazuma Kishi; Hiroki Yonemura; Shunichiro Nozawa; Ryo Sugiura; Kazumichi Kawakubo; et al. (Diagnostics, 2022)
Poor prognosis of pancreaticobiliary malignancies is attributed to intrinsic biological aggressiveness and the lack of reliable methods for early diagnosis. This study aimed to evaluate the feasibility and availability of pancreatic juice- and bile-derived cell-free DNA (cfDNA) for diagnosing pancreaticobiliary strictures. From October 2020 to February 2022, pancreatic juice or bile was obtained from 50 patients with pancreaticobiliary strictures during endoscopic retrograde cholangiopancreatography. cfDNAs extracted from the samples were analyzed using next-generation sequencing and a cancer gene panel. The obtained cfDNAs, genetic data and clinical information were analyzed for diagnosis. cfDNA concentrations in pancreatic juice were higher in the intraductal papillary mucinous neoplasm group than in the other groups, whereas those in bile were similar in all groups. In pancreatic juice, the sensitivity, specificity and positive and negative predictive values of cfDNA analyses were 33%, 100%, 100% and 71.4%, respectively, whereas those of cytological analyses were 0%, 100%, 0% and 62.5%, respectively. In bile, those of cell-free DNA analyses were 53%, 75%, 89.5% and 28.6%, respectively, whereas those of cytological analyses were 19%, 100%, 100% and 16%, respectively. In conclusion, pancreatic juice- and bile-derived cfDNA is a novel liquid biopsy tool that can diagnose pancreaticobiliary strictures.